An Analysis of Language Dominance in Students’ English Arabic Conversation at an Islamic Boarding School - Ulvia Zuhra; Masrizal Mahmud (Universitas Syiah Kuala, 2020)
The objectives of this study are to figure out what language is dominantly used by the bilingual students and what factors affect the use of one language over the other. Employing qualitative method, the study was conducted at Dayah Modern Arun Islamic Boarding School Lhokseumawe. The researcher selected the first, second and third grade of senior high school students as the respondents, with only five students selected from each grade, resulting in a total of 15 female students to be observed and interviewed. The data were collected by means of recording the students’ conversation during the lunch time and interviewing them to investigate factors that affect the use of a particular language. Using Bedore’s et al. (2012) benchmark of language dominance, students were considered bilingual dominant if their use of a language is between 80% and 60% in their dominant language and between 20% and 40% in their other language. The results indicated that the five students of the first grade were all Arabic dominant, while the five students of the second grade and the four majorities of students of the third grade were English dominant and Arabic dominant, respectedly. The results from the interview revealed that four factors influenced the dominant use of a specific language, namely preference, knowledge background, environmental factor and grammatical background.